Cake magic! : mix & match your way to 100 amazing combinations - Wright, Caroline (Workman Publishing, 2016)
"It's a simple formula for dessert bliss: batter + syrup + frosting = 100 different cakes! An innovative and remarkable easy way to bake luscious, flavorful cakes, Cake Magic! is a full-color visual cookbook-photos in the front, recipes in the back-for every cake lover, for fans of the genius of The Cake Mix Doctor series, and for home bakers who obsess over colorful cakes on Pinterest and Instagram (where cakes are consistently in the "most popular" feed). The key to the cakes' ease is the homemade Mix + Match Baking Mix - the foundation of every cake in the book. From there it's just a matter of mixing and matching batters, flavoring syrups (the secret step that makes these cake recipes so versatile), frostings, and, sometimes, topping to create unique cakes. Want something decadent and fudgy? Darkest Chocolate Cake + Milky Caramel Syrup + Malted Milk Chocolate Frosting + crushed candy bars = Candy Bar Cake. Swap in Bourbon Syrup + Cream Cheese Frosting, and you have the grown-up Drunken Tuxedo Cake. There's nothing vanilla about these vanilla cakes (Cookies + Cream Cake, Caramel-Pineapple Upside-Down Layer Cake); ethereal coconut cakes; and nutty cakes like Elvis-Peanut Butter Cake + Bacon Syrup + Nutella Frosting, topped with candied bacon. Fit for the Kind, indeed. Includes valuable baking tips, vegan and gluten-free variations, plus how to tweak the recipes to make sheet cakes, Bundt cakes, and cupcakes"--